Choking vs. clutch performance: A study of sport performance under pressure - Otten, M. (Journal of Sport & Exercise Psychology, 2009)
Choking research in sport has suggested that an athlete`s tendency to choke, versus give a better than usual (i.e., "clutch") performance depends on his or her personality, as well as on situational influences, such as a reliance on explicit (versus implicit) knowledge when pressured. The current study integrated these hypotheses and tested a structural equation model (SEM) to predict sport performance under pressure. Two hundred and one participants attempted two sets of 15 basketball free throws, and were videotaped during their second set of shots as a manipulation of pressure. Results of the model suggest that "reinvesting" attention in the task leads to greater anxiety (cognitive and somatic), which then predicts a higher level of self-focus; self-focus, then, did not lead to improved performance under pressure, whereas feelings of selfreported "perceived control" did help performance. Implications for measurement of these constructs, and their relationships with performance, are discussed.